Six degrees of freedom: Para uma Realidade Alterada - Coser, João Victor (Revista do Colóquio, 2023)
This article presents the process of creating an OPPELT (objects for performances in Low-Tech trials). In view of this, in association with augmented reality glasses, which suggest an expanded reality, OPPELT explores other paths: building [things] to inhabit the world and altering our perception of reality. Analyze the first SIX DEGREES OF FREEDOM prototype. to an Altered Reality, as well as the poetic references and purposes of the object.